IMF Research Bulletin, March 2017. (IMF Research Bulletin; IMF Research Bulletin ;, 2017)
This issue of the IMF Research Bulletin features recommended readings from IMF Publications and an update on recent IMF Working Papers and IMF Staff Discussion Notes. It also includes a special announcement welcoming Linda Tesar (University of Michigan) as the new editor of 'IMF Economic Review.' The Q and A section explores 'Seven Questions on China-Africa Relations' (Luiz Almeida, Wenjie Chen, and Oral Williams). The Research Summaries surveys 'Income Polarization in the United States' (Ali Alichi, Kory Kantenga, and Juan Sole); and 'The Future Wealth of Nations: World Trade in Services' (Prakash Loungani, Saurabh Mishra, Chris Papageorgiou, and Ke Wang).